Evolution of body composition following successful kidney transplantation is strongly influenced by physical activity: results of the CORPOS study - Moreau, Karine; Desseix, Aurélie; Germain, Christine; Merville, Pierre; Couzi, Lionel; Thiébaut, Rodolphe; Chauveau, Philippe (BMC nephrology, 2021)
Background Weight gain (mainly gain of fat mass) occurs quickly after successful kidney transplantation and is associated with metabolic complications (alterations of glycaemic control, hyperlipidaemia). Determinants of weight gain are multifactorial and are mainly related to the transplant procedure itself (glucocorticoid use, increased appetite). In the modern era of transplantation, one challenge is to limit these metabolic alterations by promoting gain of muscle mass rather than fat mass. This prospective study was performed to assess determinants of fat mass, fat-free mass and body cell mass changes after kidney transplantation with a focus on physical activity and nutritional behaviour before and after transplantation. Methods Patients were included at the time of listing for deceased donor kidney transplantation. Body composition was determined using dual X-ray absorptiometry and bioimpedance spectroscopy to assess fat mass, fat-free mass and body cell mass (= fat-free mass − extracellular water) at the time of inclusion, 12 months later, and 1, 6, 12 and 24 months after transplantation. Recall dietary data and physical activity level were also collected. Results Eighty patients were included between 2007 and 2010. Sixty-five had a complete 24-month follow-up after kidney transplantation. Fat mass, fat-free mass and body cell mass decreased during the waiting period and early after kidney transplantation. The nadirs of body cell mass and fat-free mass occurred at 1 month and the nadir for fat mass occurred at 6 months. Maximum levels of all parameters of body composition were seen at 12 months, after which body cell mass and fat-free mass decreased, while fat mass remained stable. In multivariate analysis, male recipients, higher physical activity level and lower corticosteroid dose were significantly associated with better body cell mass recovery after kidney transplantation. Conclusions Lifestyle factors, such as physical activity level, together with low dose of corticosteroids seem to influence body composition evolution following kidney transplantation with recovery of body cell mass. Specific strategies to promote physical activity in kidney transplant recipients should be provided before and after kidney transplantation.